New titanium alloys for biomaterials: A study of mechanical and corrosion properties and cytotoxicity - Kim, T.-I.; Han, J.-H.; Lee, I.-S.; Lee, K.-H.; Shin, M.-C.; Choi, B.-B. (IOS Press, 1997)
Three new titanium alloys with Zr, Nb, Ta, Pd and In as alloying elements were developed and compared with currently used implant metals, namely, pure Ti and Ti-6Al-4V alloy, in terms of mechanical and corrosion properties, and cytotoxicity. New alloys showed comparable mechanical properties with that of the Ti-6Al-4V alloy, but increased corrosion potential, somewhat decreased breakdown potential and increased corrosion rate. There were no significant differences in cell growth on the surface of the various metal specimens, indicating that the cells cannot differentiate between the passivated surfaces of the various Ti metals. ？ 1997 - IOS Press. All rights reserved.
Keywords: alloy; indium; niobium; palladium; tantalum; titanium; zirconium; article; biomechanics; corrosion; hardness; human; materials testing; prosthesis; standard; tooth implantation; toxicity testing; Alloys; Biomechanics; Corrosion; Dental Implantation, Endosseous; Dental Implants; Hardness Tests; Humans; Indium; Materials Testing; Niobium; Palladium; Prosthesis Design; Tantalum; Titanium; Toxicity Tests; Zirconium